Pengaruh Kegiatan Senam Sorak Hore Terhadap Perkembangan Motorik Kasar Anak Kelompok B di TKIT Al-Islam Sine - Yoni Martiana, Dwi (Jurnal Jendela Bunda Program Studi PG-PAUD Universitas Muhammadiyah Cirebon, 2024)
This study aims to determine the effect of cheerleading activities ("senam sorak hore") on the development of gross motor skills and how significant this influence is on the gross motor development of Group B children at TKIT Al-Islam Sine. The population in this study consisted of Group B children aged 5-6 years at TKIT Al-Islam Sine in the Sine District of Ngawi Regency for the Academic Year 2023/2024, with a total of 34 students. The sample used in this study was Group B for the academic year 2023/2024, consisting of 34 students, considering that the gross motor skills of students in this group were still relatively low. The results showed that the average score of gross motor skills of Group B children at TKIT Al-Islam Sine before and after being given treatment, namely from the average score before treatment of 44.11, while the average score after treatment showed an increase to 65.92. Furthermore, by examining the results of the t-test formula for small interrelated samples in this study, it showed that the sig. value (2-tailed) was 0.00 because the significance value of the 2-tailed test was less than 0.05, thus the data can be stated that Ho is rejected and Ha is accepted, meaning the alternative hypothesis is accepted, and the null hypothesis is rejected. It can be concluded that there is a significant effect of cheerleading activities on the gross motor skills of Group B children at TKIT Al-Islam Sine.